FAKTOR RISIKO TERHADAP KEUNTUNGAN USAHA RUMAH KAYU CV RAJAWALI TUNGGAL PERKASA DI KELURAHAN WOLOAN SATU KECAMATAN TOMOHON BARAT (Risk Factors for the Profit of the Wooden Houses Business CV Rajawali Tunggal Perkasa in Woloan Satu Village, West Tomohon District) - Felisia Angel Tanie; Leonardus Ricky Rengkung; Jelly R. D. Lumingkewas (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2020)
This study aims to determine the risk factors for the profitability of CV Rajawali Tunggal Perkasa's wooden house business in Woloan 1 Village, Tomohon Barat District based on the types of houses. The types of houses available are small (30 m2), medium (63 m2), large (120 m2) and extra large (198 m2) types. The results showed that the greater the type of wooden house produced, the higher the risk factors contained in it so that it affects profits. The highest risk factor is found in the extra large type because it obtains 16 risks out of 17 total risks, which is equivalent to 94.12%, so that the business only receives a profit of Rp 16,758,702, the lowest compared to other types. It can be concluded that the larger the size of the house being produced, the higher the risk contained therein, thereby affecting profits.Keywords: risk, risk factors, profit, wooden house